Zinc oxide nanoparticles alter the wheat physiological response and reduce the cadmium uptake by plants. (November 2018) - Hussain, Afzal; Ali, Shafaqat; Rizwan, Muhammad; Zia ur Rehman, Muhammad; Javed, Muhammad Rizwan; Imran, Muhammad; Chatha, Shahzad Ali Shahid; Nazir, Rashid
Abstract: An experiment was performed to explore the interactive impacts of zinc oxide nanoparticles (ZnO NPs) and cadmium (Cd) on growth, yield, antioxidant enzymes, Cd and zinc (Zn) concentrations in wheat ( Triticum aestivum ). The ZnO NPs were applied both in Cd-contaminated soil and foliar spray (in separate studies) on wheat at different intervals and plants were harvested after physiological maturity. Results depicted that ZnO NPs enhanced the growth, photosynthesis, and grain yield, whereas Cd and Zn concentrations decreased and increased respectively in wheat shoots, roots and grains. The Cd concentrations in the grains were decreased by 30–77%, and 16–78% with foliar and soil application of NPs as compared to the control, respectively. The ZnO NPs reduced the electrolyte leakage while increased SOD and POD activities in leaves of wheat. It can be concluded that ZnO NPs (levels used in the study) could effectively reduce the toxicity and concentration of Cd in wheat whereas increase the Zn concentration in wheat. Thus, ZnO NPs might be helpful in decreasing Cd and increasing Zn biofortification in cereals which might be effective to reduce the hidden hunger in humans owing the deficiency of Zn in cereals. Graphical abstract: Image 1 Highlights: Zinc oxide nanoparticles (ZnO NPs) increased the wheat yield under cadmium (Cd) stress. ZnO NPs increased chlorophyll contents and gas exchange attributes of wheat under Cd stress. ZnO NPs enhanced antioxidant enzyme activities in wheat leaves under Cd stress. ZnO NPs reduced the Cd concentrations and increased zinc concentrations in wheat. Abstract : ZnO NPs increased the growth and yield while decreased the Cd in wheat grains.